HUBUNGAN KONDISI SANITASI DASAR RUMAH TANGGA DENGAN KEJADIAN DIARE PADA BALITA DI DESA KUTETANYUNG, KUTE LINTANG, DELUNG ASLI, BLANG SENTANG, TINGKEM ASLI DI WILAYAH KERJA PUSKESMAS SIMPANG TIGA TAHUN 2024 - Yanti, Marida; Saipullah; Muzaffar (Jurnal Ilmiah Cerebral Medika, 2025)
ABSTRACT Toddlers are the most susceptible to diarrhea because toddlers have a weaker immune system than adults. Diarrhea can occur due to poor sanitation. The type of research uses analytical surveys. The research method used cross sectional, the total population was 338 people, and the sample was 79 people. Using random sampling, data analysis uses the chi-square test. The results of the chi-square test analysis obtained a significant value of toilet ownership of 0.004<0.05, clean water supply of 0.045<0.05. Waste disposal facilities of 0.021<0.05. Waste disposal facilities of 0.012<0.05 Therefore, it can be concluded that there is a significant relationship between household sanitation conditions and the incidence of diarrhea in toddlers in the working area of the Bukit Health Center of Kute Tanyung, Kute Lintang, Delung Asli, Blang Sentang, and Tingkem Asli villages in 2024. It is hoped that the community can improve household sanitation so that the incidence of diarrhea decreases and is free from diseases caused by poor sanitations. Keywords : Sanitations, Diarrhea